Association of cyclooxygenase-2 genetic variant with cardiovascular disease - Ross, Stephanie; Eikelboom, John; Anand, Sonia S.; Eriksson, Niclas; Gerstein, Hertzel C.; Mehta, Shamir; Connolly, Stuart J.; Rose, Lynda; Ridker, Paul M.; Wallentin, Lars; Chasman, Daniel I.; Yusuf, Salim; et al. (European heart journal, 2014)
A genetic variant (rs20417) of the PTGS2 gene, encoding for COX-2, has been associated with decreased COX-2 activity and a decreased risk of cardiovascular disease (CVD). However, this genetic association and the role of COX-2 in CVD remain controversial. The association of rs20417 with CVD was prospectively explored in 49 232 subjects (ACTIVE-A, CURE, epiDREAM/DREAM, ONTARGET, RE-LY, and WGHS) and the effect of potentially modifiable risk factors on the genetic association was further explored in 9363 INTERHEART participants. The effect of rs20417 on urinary thromboxane and prostacyclin metabolite concentrations was measured in 117 healthy individuals. Carriage of the rs20417 minor allele was associated with a decreased risk of major CVD outcomes (OR = 0.78, 95% CI: 0.70-0.87; P = 1.2 × 10(-5)). The genetic effect was significantly stronger in aspirin users (OR: 0.74, 95% CI: 0.64-0.84; P = 1.20 × 10(-5)) than non-users (OR: 0.87, 95% CI: 0.72-1.06; P = 0.16) (interaction P-value: 0.0041). Among patients with previous coronary artery disease (CAD), rs20417 carriers had a stronger protective effect on risk of major adverse events when compared with individuals without previous CAD (interaction P-value: 0.015). Carriers had significantly lower urinary levels of thromboxane (P = 0.01) and prostacyclin (P = 0.01) metabolites when compared with non-carriers. The rs20417 polymorphism is associated with a reduced risk of major cardiovascular events and lower levels of thromboxane and prostacyclin. Our results suggest that a genetic decrease in COX-2 activity may be beneficial with respect to CVD risk, especially, in higher risk patients on aspirin.